Síntese de 1-alquil-4-aminoalquil-2-trifluormetil-1H-pirróis e 1,2,3- triazóis derivados - Zachow, Lucimara Lais (2020)
In the present work, it was carried out a study of the reactivity of 5-bromo-1,1,1-trifluoro- 4-methoxypent-3-en-2-one (5-bromo enone) towards primary aliphatic amines, which furnishes as products two novel series of N-substituted 4-amino-2-trifluoromethyl-1H-pyrroles (pyrroles) and 5-(amino(1-amino-5-(trifluoromethyl)-1H-pyrrol-3-yl)amino)-4-(amino)-1,1,1- trifluoropent-3-en-2-ones (enamine pyrroles). The pyrroles were obtained through the reaction of 5-bromo enone with excess of the primary aliphatic amine in refluxing acetonitrile for 2 hours (13 examples, yields 30 – 90%), while the enamine pyrroles were obtained using a molar ratio of 1.0:1.5 of 5-bromo enone/primary amine, respectively, in a solventless-sealed tube procedure at 120 °C for 15 min (7 examples, yields 7 – 78%). In a second part of the work, derivatization reactions were carried out in order to promote further functionalization of the N-substituted 4-amino-2-trifluoromethyl-1H-pyrroles, obtained in the previous step, with different alkylating agents, such as methyl iodide, allyl bromide and propargyl bromide using acetone as solvent, under reflux conditions for 2 hours. Through the N-alkylation reactions, 11 tertiary aliphatic amines bearing three different substituents (one being the pyrrole core), were obtained in yields up to 90%. Following this, the propargylic pyrroles were employed in the synthesis of a series of 1,2,3-triazoles, through the [3+2] cycloaddition reaction using benzylic azides, and, 7 examples with yields 72 – 91% were obtained. In addition, the synthesis of a tri-heterocyclic scaffold containing the pyrrole, 1,2,3- triazole and pyrimidine nuclei, was carried out using the propargylic pyrrole and 4- (azidomethyl)-2-(methylthio)-6-(trifluoromethyl)pyrimidine, at 80% yield, under the same reaction conditions.